2014
DOI: 10.1186/1479-5876-12-102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of elevated serum soluble CD40 ligand levels as a diagnostic and prognostic tumor marker for pancreatic ductal adenocarcinoma

Abstract: BackgroundCD40-CD40 ligand (CD40L) interaction is considered to contribute to the promotion of prothrombotic responses and production of angiogenesis-associated factor in addition to adaptive immune responses. Recently, the role of soluble CD40L (sCD40L) has gained interest in cancer, although its exact functions remain unknown. This study evaluated the clinical significance of sCD40L in patients with pancreatic ductal adenocarcinoma (PDAC) and validated its utility as a PDAC diagnostic and prognostic biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The previous report has shown that high sCD40L concentrations are associated with short survival time in patients with pancreatic ductal adenocarcinoma [32]. The current study analyzed biological and clinical variables in 312 patients with NPC, and Kaplan-Meier survival analysis and Cox proportional hazards regression models indicated that NPC patients with high plasma sCD40L concentrations had poorer prognosis than those with low plasma sCD40L concentrations.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The previous report has shown that high sCD40L concentrations are associated with short survival time in patients with pancreatic ductal adenocarcinoma [32]. The current study analyzed biological and clinical variables in 312 patients with NPC, and Kaplan-Meier survival analysis and Cox proportional hazards regression models indicated that NPC patients with high plasma sCD40L concentrations had poorer prognosis than those with low plasma sCD40L concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…This positive expression of CD40 is associated highly with lymphatic metastasis and tumor stage in gastric cancer patients [47]. sCD40L is produced at high concentrations in patients with pancreatic ductal adenocarcinoma, lung cancer and NPC [32][33][34]. This study found that enhanced pretreatment plasma sCD40L concentrations were correlated highly with tumor classification, lymph node classification and tumor node metastasis stage.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations